In vitro antioxidant activity and antimicrobial activity against biofilm forming bacteria by the pigment from Desert soil Streptomyces sp D25 - Manikkam Radhakrishnan, Venugopal Gopikrishnan, Ganesan Vijayalakshmi, Vanaja Kumar (Journal of Applied Pharmaceutical Science, 2016)
Streptomyces from rare ecosystems is the promising source for secondary metabolites exhibiting diverse biological activities. The present study reports the antioxidant activity and antimicrobial activity against biofilm forming bacteria by the pigment produced from Desert soil Streptomyces sp. D25. Crude pigment from the Streptomyces sp D25 was produced by agar surface fermentation using yeast extract malt extract agar and extracted using ethyl acetate. Antioxidant activity of pigment was tested at 100-500µg/ml concentration by DPPH and nitric acid scavenging assay. Antimicrobial activity against the biofilm forming bacteria was tested by disc diffusion method. The Streptomyces pigment showed 35.63% and 96.19% free radical scavenging activity in DPPH assay and nitric oxide assay, respectively. The results of radical scavenging activity of pigment in DPPH and nitric oxide assay showed its antioxidant potential. In antimicrobial assay, the pigment showed 10-20 mm inhibition against biofilm forming bacteria at 25µg/ml. Further in vivo studies on this Streptomyces pigment pave the way for its biomedical applications.
Keywords: Streptomyces, antioxidant, DPPH method, biofilm and antimicrobial activity.